A cidade do Crato na rede urbana cearense: papel e importância na dinâmica urbana do CRAJUBAR - Sousa, Raimunda Aurilia Ferreira de (2015)
The study of urban-regional dynamics of cities and the role that develops within of the groups of cities is an important theme in geographical studies. These spaces gain new forms and contents when start developing different activities and urban functions. In this sense, this work consists in discussing the set of functions and urban activities in the city of Crato-Ce. It has as a reference research focus its situation/position opposite the group of cities represented by Juazeiro do Norte and Barbalha. This urban agglomeration is responsible for the strong regional influence of Cariri in Ceará urban hierarchy consolidating its position as the largest example of complementary functions in the state of Ceará. With regard to Crato, natural attributes, economic and political that had once made it play the role of absolute urban-regional command in Cariri and area of influence. From the importance of Crato initial perspective on urban dynamics, in which is part of, the central purpose of the research is to glimpse different moments of this center and stablished urban roles, to identify changes, continuity and activity breaks presented in time and space. It´s used as the initial time frame analysis the late nineteenth century and through central landmarks to understand what the place of Crato in the realization of urban functions and constitution of the Metropolitan region of Cariri- RMC. The presence of new social agents and respectively of new space processes in the cluster did Crato flow back in the set of activities developed in the intra and inter-urban scale. The mergence of Juazeiro has a lot to explain to this urban condition of Crato that since the insurrection of Juazeiro divides strength and loses space in the assembly constituted by complementarity of functions. It´s considered legitimate to understand these changes in view of the importance and relief of Cariri and specially Crajubar in different scales of urban-regional analysis.